Mirabegron in Overactive Bladder and Its Role in Exit Strategy After Botulinum Toxin Treatment in Children - Tan, Denise Jia Yun; Weninger, Julia; Goyal, Anju (Frontiers in Pediatrics, 2022)
Purpose Mirabegron is a recent addition to the management options of overactive bladder (OAB) in children. The purpose of this study was to ascertain the role of Mirabegron in the treatment algorithm of therapy resistant OAB especially after botulinum toxin. Methods Case notes of all children receiving Mirabegron between July 2017 and February 2020 were reviewed. Results 41 children (21 females, 20 males), mean age 12.6 [8-17] years old, commenced Mirabegron: 35 idiopathic OAB, 6 neuropathic OAB. Mean duration of treatment was 20.7 [3-45] months. 24 (59%) had Mirabegron after partial/no response to anticholinergics and 17 (41%) patients had Mirabegron subsequent to Botulinum Toxin A(BtA) as an exit strategy. 35 (85%) patients had combination therapy (Mirabegron and anticholinergics), 6 (15%) patients had Mirabegron only. Fourteen (34%) had complete response, 17 (41%) had partial response and 10 (24%) had no response. Side effects were reported in 7 (17%) patients with discontinuation necessitated in 3. Conclusion Mirabegron when used alone or in combination with anticholinergics resulted in complete/partial response in 76% of anticholinergic therapy resistant OAB. In addition to being an important step in treatment escalation after no/partial response to anticholinergics, it has a crucial role in the exit strategy for recurring symptoms after BtA wears off.